Women in Fintech : As Leaders and Users - Khera, Purva (IMF Working Papers; Working Paper, 2022)
While digital financial services have made access to finance easier, faster, and less costly, helping to broaden digital financial inclusion, its impact on gender gaps varies across countries. Moreover, women leaders in the fintech industry, although growing, remain scarce. This paper explores the interaction between 'women' and 'fintech' by examining: (i) the role of women leaders on firm-level performance in the fintech industry; and (ii) the determinants of gender gaps in the usage of digital services to better understand the cross-country differences. Results indicate that greater gender diversity in the executive board is associated with better performance of fintech firms.With regard to determinants of the gender gaps in the usage of digital financial services, we find that higher financial and digital literacy of women is associated with lower gender gaps in digital financial inclusion, and that socio-cultural factors also play a key role.